The Effect of Perineurotomy on Nerve Regeneration in Diabetic Rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Background: One of the main causes of diabetic neuropathy is endoneurial edema, which increases the internal pressure of the perineurium, which has a tight structure. The treatment used to reduce internal pressure is perineurotomy, in which a surgical incision is made into the perineurium. Methods: Forty male Sprague-Dawley rats were used in the study. They were classified into four groups. Streptozotocin-induced diabetes was created in groups III and IV. The sciatic nerve was transected and repaired epineurally in all groups. Perineurotomy was performed additionally in group II and IV to the sciatic, peroneal, tibial, and sural nerves from the most proximal side to their most distal ends. The sciatic function indices were calculated for functional assessment. Light and electron microscopic evaluations were performed for morphometric assessment. In addition, the myelinated and degenerated fibers were counted in all groups. Results: The sciatic function indices of the diabetic perineurotomy group were found to be significantly higher than those of the other groups (p < 0.05). Based on the myelinated fiber counts, there was insignificant difference between group I and group II, whereas the difference was significant (p < 0.05) between group III and group IV. Presence of peripheric nerves in light microscopic evaluation revealed normal characteristics of myelinated fibers in group I and group II. The myelinated axon profile in group IV was similar to that of groups I and II in electron microscopic evaluation. Conclusion: It is concluded that perineurotomy may be established as a useful adjunctive procedure for nerve repair in diabetic patients. (Plast. Reconstr. Surg. 130: 651e, 2012.)
Keywords: PERIPHERAL-NERVES; DECOMPRESSION PROCEDURES; SURGICAL DECOMPRESSION; FIBER MATURATION; TIBIAL NERVE; DOUBLE CRUSH; BODY GROWTH; NEUROPATHY; ABNORMALITIES; OPTIMISM